Freshness detection test strip of hyperbranched gold-silver-copper nanoclusters, preparation method and application

CN122487310BActive Publication Date: 2026-10-16INST OF AGRO FOOD SCI & TECH CHINESE ACADEMY OF AGRI SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610977756.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-16
Estimated Expiration
2046-07-02

AI Technical Summary

Technical Problem

然而,现有技术在超支化聚合物辅助制备金属纳米簇方面仍存在明显不足

Benefits of technology

其一、本发明采用一锅法制备超支化金银铜纳米簇,以自制的四苯乙烯基超支化聚酰胺-胺为配体和稳定剂、青霉胺为温和还原剂,合成步骤简便,无需严苛的高温高压或惰性气氛条件,所得超支化聚合物富含氨基配位位点,可有效锚定金银铜三元金属离子并抑制纳米簇团聚,从而获得比单金属或双金属体系更高的荧光量子产率和更灵敏的响应特性,为硫化氢的高效检测奠定了材料基础保证了纳米簇的高荧光量子产率和优异的胶体稳定性,为后续制备高性能试纸条提供理想的荧光传感材;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122487310B_ABST
    Figure CN122487310B_ABST
Patent Text Reader

Abstract

The application discloses a kind of hyperbranched gold silver copper nanocluster freshness detection test strips, method and application, belong to food safety rapid detection technical field.The technical problem that the present meat freshness detection method is tedious, cost is high, and single metal nanocluster fluorescence quantum yield is low, poor stability, difficult to realize on-site rapid nondestructive detection, the addition product is prepared by reacting tri (2-aminoethyl) amine with 4-glycidyl ether tetraphenyl ethylene, then hyperbranched polyamide-amines are obtained by Michael addition polymerization of diacryl hexanediamine, which is used as ligand and stabilizer, with penicillamine as reducing agent, with chloroauric acid, silver nitrate, copper nitrate by one-pot method to prepare hyperbranched gold silver copper nanoclusters, and are immobilized on watman test paper to prepare test strips.The test strip can realize the rapid, visual detection of fresh meat freshness marker hydrogen sulfide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rapid food safety testing technology. More specifically, this invention relates to a hyperbranched gold, silver, and copper nanoclusters freshness test strip, its preparation method, and its application; it is particularly suitable for rapid, visual fluorescence detection of hydrogen sulfide, a marker of meat freshness. Background Technology

[0002] As a major contributor of high-quality protein in the human diet, meat supports human health with its high biological value protein. However, the abundance of protein also provides a breeding ground for rapid microbial growth, making meat highly susceptible to spoilage during storage and distribution. In this complex spoilage process, microorganisms decompose sulfur-containing amino acids (such as cysteine ​​and methionine) in meat through enzymatic hydrolysis, gradually releasing volatile sulfur compounds such as hydrogen sulfide and thiols. Among these, hydrogen sulfide, with its characteristic rotten egg odor and concentration changes highly correlated with the spoilage process, is recognized as a key chemical marker of meat freshness deterioration. Therefore, developing efficient, sensitive, and convenient hydrogen sulfide detection technology is of significant practical importance for ensuring food safety, reducing food waste, and improving supply chain management.

[0003] Currently, hydrogen sulfide detection mainly relies on traditional methods such as gas chromatography, ultraviolet spectrophotometry, and electrochemical sensors. While gas chromatography offers high separation efficiency and accurate quantification, it typically requires expensive equipment and specialized personnel, and the sample pretreatment process is cumbersome and time-consuming, making it difficult to meet the needs of rapid on-site detection. Ultraviolet spectrophotometry often requires complex colorimetric reaction systems, and its detection sensitivity is significantly affected by the sample matrix. Although electrochemical sensors offer some portability, the electrode surface is susceptible to environmental contamination, resulting in insufficient long-term stability, and the accuracy and repeatability of hydrogen sulfide quantification need improvement. These traditional methods, due to their cumbersome operation, high cost, and long processing time, greatly limit their application in real-time on-site detection of meat freshness.

[0004] Given the numerous shortcomings of traditional detection methods, fluorescent nanomaterials have attracted significant attention in the fields of chemical sensing and biological detection in recent years due to their outstanding advantages such as high sensitivity, fast response speed, and ease of operation. Among various fluorescent nanomaterials, metal nanoclusters (MNCs) exhibit unique advantages due to their ultra-small size (typically less than 3 nm), good photostability, large Stokes shift, and excellent biocompatibility. However, currently widely studied single-metal nanoclusters, such as gold nanoclusters (AuNCs) and silver nanoclusters (AgNCs), generally suffer from problems such as low fluorescence quantum yield, poor luminescence stability, and limited means of optical performance modulation. Although copper nanoclusters are inexpensive, their fluorescence intensity and stability are usually weaker, and they are easily oxidized. These inherent limitations make it difficult for single-metal nanoclusters to meet the stringent requirements of high sensitivity, high stability, and wide response range in practical applications. Multi-metal nanocluster systems, represented by gold-silver-copper trimetallic nanoclusters, can achieve precise control of fluorescence performance through electronic interactions and synergistic effects among the three metals. This results in higher fluorescence quantum yield and more sensitive response characteristics compared to single-metal or bimetallic systems, laying the material foundation for efficient detection of hydrogen sulfide.

[0005] To further enhance the stability and functionality of metal nanoclusters, selecting suitable ligands is crucial. Hyperbranched polyamide-amines are a class of highly branched three-dimensional spherical polymers with abundant terminal amino groups and internal cavities in their molecular structure, which can effectively stabilize metal nanoclusters through coordination and spatial confinement effects. However, existing technologies still have significant shortcomings in the preparation of metal nanoclusters assisted by hyperbranched polymers. For example, Chinese patent CN101225227B discloses a method for preparing hyperbranched polyamide-amine and metal nanocomposites, which uses vinyl-terminated hyperbranched polyamide-amine as a template to prepare gold or silver nanoparticles without the addition of an external reducing agent. However, this method can only prepare single gold or silver nanoparticles and cannot achieve the controllable preparation of ternary metal nanoclusters, making it difficult to leverage the synergistic effect between multiple metals. Furthermore, its metal nanocomposites are mainly used in the antibacterial field and do not involve functional applications such as fluorescence sensing and hydrogen sulfide detection. For example, Chinese patent CN114047169A discloses a method for detecting hydrogen sulfide based on metal nanoclusters. This method uses the fluorinated ligand 2,3,5,6-tetrafluorobenzylthiophenol as a reducing agent to induce copper ions to form copper nanoclusters. The self-assembly-induced luminescence properties of these nanoclusters are then used to achieve fluorescence detection of hydrogen sulfide. However, this method is limited to single-metal copper nanocluster systems. Due to the low fluorescence quantum yield and easy oxidation of copper nanoclusters, its detection sensitivity and signal stability are insufficient to meet the requirements for detecting trace amounts of hydrogen sulfide in complex food matrices. Furthermore, while ratiometric fluorescence sensing systems based on gold-copper bimetallic nanoclusters improve the sensing performance of single-metal nanoclusters to some extent, their synergistic regulation of metal components, signal stability after strip immobilization, and practical application effects in meat freshness detection still require further verification and optimization.

[0006] In summary, existing technologies for rapid detection of meat freshness still face the following unresolved challenges: traditional chromatographic and spectroscopic methods are cumbersome and costly, making them unsuitable for on-site testing; single-metal nanoclusters exhibit low fluorescence quantum yields, poor optical stability, and insufficient detection sensitivity; bimetallic nanoclusters have limited intermetallic synergistic regulation capabilities, making it difficult to achieve precise optimization of fluorescence performance; and metal nanoparticle systems prepared using hyperbranched polyamide-amine as templates either involve only single metals or only single functional applications, failing to simultaneously maximize the synergistic effects of ternary metals and achieve functional designs targeting hydrogen sulfide-specific fluorescence responses. Developing a rapid on-site test strip that is easy to prepare, cost-effective, exhibits excellent fluorescence performance, and demonstrates high sensitivity and selectivity to hydrogen sulfide gas remains a key challenge that urgently needs to be addressed in this field. Summary of the Invention

[0007] One object of the present invention is to solve at least the above-mentioned problems and to provide at least the advantages that will be described later.

[0008] Another objective of this invention is to provide a method for preparing a test strip for the freshness of hyperbranched gold, silver, and copper nanoclusters. This method involves the synergistic preparation of gold, silver, and copper ternary metal nanoclusters using hyperbranched polyamide-amine and penicillamine, and then immobilizing them on test strips. The preparation method is simple and cost-effective. The resulting test strips utilize the excellent fluorescence properties imparted by the synergistic effect between the ternary metals and the stabilizing effect of the hyperbranched polymer, offering advantages such as high sensitivity, rapid response, convenient operation, and suitability for on-site non-destructive testing.

[0009] To achieve these objectives and other advantages according to the present invention, a method for preparing a freshness test strip for hyperbranched gold, silver, and copper nanoclusters is provided, comprising: S1. Tri(2-aminoethyl)amine, 4-glycidyl ether tetraphenylene, and methanol are mixed in a molar ratio of 1:4~6:90~120 and reacted at 65~80 °C for 21~27 h under nitrogen protection to obtain the 4-glycidyl ether tetraphenylene-tri(2-aminoethyl)amine adduct. S2. The 4-glycidyl ether tetraphenylethylene-tris(2-aminoethyl)amine adduct obtained in S1 is mixed with bisacryloylhexanediamine at a molar ratio of 3:2.2 and subjected to Michael addition polymerization at 21-27 °C for 90-102 h under nitrogen protection to obtain hyperbranched polyamide-amine. S3. Mix chloroauric acid solution, silver nitrate solution and copper nitrate solution at a metal ion molar ratio of 1:1:1 to obtain a gold-silver-copper ternary metal ion mixture. S4. Add the hyperbranched polyamide-amine obtained in S2 as a ligand and stabilizer to the gold-silver-copper ternary metal ion mixture obtained in S3. After stirring evenly, add penicillamine as a reducing agent and stir at room temperature for 1-2 h. After the reaction is completed, centrifuge to remove the supernatant, purify the precipitate and freeze dry at -40 to -50℃ to obtain hyperbranched gold-silver-copper nanocluster powder. S5. Prepare a solution from the hyperbranched gold, silver and copper nanoclusters powder obtained in S4, and uniformly drop it onto Waterman test paper. Dry at room temperature to obtain the hyperbranched gold, silver and copper nanoclusters freshness test strip. In step S4, the molar ratio of gold ions, silver ions, copper ions, hyperbranched polyamide-amine, and penicillamine is 1:1:1:0.04:108.

[0010] Preferably, the bisacryloylhexanediamine in step S2 is prepared by the following method: Sodium hydroxide and hexamethylenediamine were mixed evenly. Acryloyl chloride was slowly added dropwise to the mixture of sodium hydroxide and hexamethylenediamine under stirring in an ice bath at 0°C. The molar mixing ratio of sodium hydroxide, hexamethylenediamine and acryloyl chloride was (1.8~2.2):1:(1.8~2.2).

[0011] Preferably, in step S5, the hyperbranched gold, silver, and copper nanoclusters are prepared into a solution with a concentration of 1-4 mg / mL.

[0012] The present invention further claims a hyperbranched polyamide-amine, which is prepared by Michael addition polymerization of 4-glycidyl ether tetraphenyl-tris(2-aminoethyl)amine adduct and bisacryloylhexanediamine, wherein the molar ratio of 4-glycidyl ether tetraphenyl-tris(2-aminoethyl)amine adduct to bisacryloylhexanediamine is 3:2.2.

[0013] The present invention further claims a hyperbranched gold-silver-copper nanocluster, which is prepared by steps S1 to S4 of the method described above. The hyperbranched gold-silver-copper nanocluster is formed by a one-pot reaction of gold ions, silver ions and copper ions using hyperbranched polyamide-amine as ligand and stabilizer and penicillamine as reducing agent. The hyperbranched gold-silver-copper nanocluster exhibits dual emission fluorescence characteristics at 483 nm and 624 nm under 360 nm excitation.

[0014] The present invention further claims a test strip for the freshness of hyperbranched gold, silver and copper nanoclusters, wherein the test strip is prepared by the same method described above.

[0015] This invention further claims the application of the hyperbranched gold-silver-copper nanocluster freshness test strip in the detection of hydrogen sulfide, a marker of freshness in fresh meat. After the hyperbranched gold-silver-copper nanocluster freshness test strip reacts with hydrogen sulfide, it simultaneously generates a fluorescence channel response with a decrease in fluorescence intensity and a colorimetric channel response with the test strip color changing from light to yellow. The fluorescence channel response refers to the dual emission fluorescence characteristics at 483 nm and 624 nm under 360 nm excitation.

[0016] This invention further claims a method for detecting hydrogen sulfide, a marker of freshness in fresh meat, using the aforementioned hyperbranched gold-silver-copper nanocluster freshness test strip, comprising: A1. Sodium hydrosulfide solution of hydrogen sulfide standard at different concentrations was added dropwise to hyperbranched gold-silver-copper nanoclusters solution and incubated at room temperature for 10-15 min. The solution was excited at a wavelength of 360 nm, and the fluorescence intensity of the hyperbranched gold-silver-copper nanoclusters solution at 483 nm and 624 nm was recorded. A standard curve of fluorescence intensity ratio at 483 nm and 624 nm versus hydrogen sulfide concentration was prepared. A2. Prepare sodium hydrosulfide solutions of hydrogen sulfide standard at different concentrations, place them in a sealed container, and allow the hyperbranched gold, silver, and copper nanoclusters freshness test strip to contact the gas in the container. Incubate at room temperature for 10-16 hours, and photograph and record the color changes of the hyperbranched gold, silver, and copper nanoclusters freshness test strip under fluorescent light and 365nm ultraviolet light. Extract the RGB values ​​and prepare a standard curve of color difference versus hydrogen sulfide concentration for the hyperbranched gold, silver, and copper nanoclusters freshness test strip under fluorescent light, or a standard curve of red / green channel ratio versus hydrogen sulfide concentration for the hyperbranched gold, silver, and copper nanoclusters freshness test strip under ultraviolet light. A3. Place the fresh meat sample to be tested in a sealed container, and allow the hyperbranched gold-silver-copper nanocluster freshness test strip to contact the gas inside the container. Incubate at room temperature for 10-15 min. Excite the test strip at a wavelength of 360 nm and record the fluorescence intensity ratio at 483 nm and 624 nm. Alternatively, place the fresh meat sample to be tested in a sealed container, and allow the hyperbranched gold-silver-copper nanocluster freshness test strip to contact the gas inside the container. Incubate at room temperature for 10-16 h. Take photos to record the color changes of the hyperbranched gold-silver-copper nanocluster freshness test strip under fluorescent light and 365 nm ultraviolet light, and extract the RGB values. A4. Compare the fluorescence intensity ratio at 483 nm and 624 nm measured in step A3, or the color difference of the hyperbranched gold, silver and copper nanoclusters freshness test strip under fluorescent light, or the red / green channel ratio of the hyperbranched gold, silver and copper nanoclusters freshness test strip under ultraviolet light, with the corresponding standard curve obtained to obtain the hydrogen sulfide content in the sample to be tested, thereby determining the freshness of fresh meat.

[0017] The present invention further claims a method for detecting hydrogen sulfide using ratiometric fluorescence, which uses the hyperbranched gold-silver-copper nanocluster freshness test strip, is excited at a wavelength of 360 nm, records the ratio of fluorescence intensity at 483 nm to 624 nm, and quantitatively detects the hydrogen sulfide concentration based on the change in the ratio of fluorescence intensity at 483 nm to 624 nm.

[0018] This invention further claims a ratiometric method for detecting hydrogen sulfide, which involves contacting the hyperbranched gold-silver-copper nanocluster freshness test strip with the hydrogen sulfide gas to be tested or the volatile gas from a fresh meat sample, photographing and recording the color change of the test strip and extracting the RGB values, using the color difference value of the hyperbranched gold-silver-copper nanocluster freshness test strip as a response signal, and quantitatively detecting the hydrogen sulfide concentration based on the change in the color difference value.

[0019] The present invention has at least the following beneficial effects: Firstly, this invention employs a one-pot method to prepare hyperbranched gold, silver, and copper nanoclusters. Using self-made tetraphenylethylene-based hyperbranched polyamide-amine as ligand and stabilizer, and penicillamine as a mild reducing agent, the synthesis steps are simple, requiring no harsh high-temperature, high-pressure, or inert atmosphere conditions. The resulting hyperbranched polymer is rich in amino coordination sites, which can effectively anchor gold, silver, and copper ternary metal ions and inhibit nanocluster aggregation, thereby obtaining a higher fluorescence quantum yield and more sensitive response characteristics than single-metal or bimetallic systems. This lays the material foundation for the efficient detection of hydrogen sulfide and ensures the high fluorescence quantum yield and excellent colloidal stability of the nanoclusters, providing an ideal fluorescent sensing material for the subsequent preparation of high-performance test strips. Secondly, the hyperbranched gold-silver-copper nanoclusters prepared in this invention exhibit dual emission fluorescence characteristics at 483 nm and 624 nm under a single excitation wavelength. After reacting with hydrogen sulfide, they not only produce a response of decreased fluorescence intensity, but also a visual colorimetric response of the test strip color changing from light to yellow. The dual-channel signal output mode does not rely on large instruments, and the color change can be interpreted by the naked eye or the ratio signal can be read with the help of simple fluorescence equipment, which greatly improves the convenience, reliability and anti-interference ability of on-site detection. Thirdly, the hydrogen sulfide detection method established by the present invention based on the test strip can flexibly use the dual emission fluorescence ratio or the color difference value of the test strip for quantitative analysis, realizing the dual-mode signal output of fluorescence and colorimetry. The detection limit for hydrogen sulfide is as low as 0.4282 μM, and the sensitivity is significantly better than that of conventional single metal or bimetal nanocluster sensing systems. The detection process only requires exposing the test strip to the sample gas for 10-15 minutes, which is extremely simple to operate and fully meets the timeliness requirements of rapid and non-destructive on-site detection of fresh meat freshness. Fourth, the ratiometric fluorescence detection method provided by this invention uses the fluorescence intensity ratio of the dual emission peaks at 483 nm and 624 nm as the quantitative basis. It effectively eliminates the interference of non-target factors such as excitation light intensity fluctuations, changes in environmental conditions, and local concentration differences of the probe on the detection signal by utilizing an internal standard self-calibration mechanism. Compared with single-wavelength fluorescence detection, it significantly improves the accuracy, reproducibility, and signal-to-noise ratio of quantitative analysis, and shows higher reliability in the detection of trace hydrogen sulfide in complex food matrices.

[0020] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the synthesis route of the hyperbranched gold-silver-copper nanoclusters described in one embodiment of the present invention; Figure 2 The fluorescence spectrum of the hyperbranched polyamide-amine described in another embodiment of the present invention is shown. Figure 3 The fluorescence spectrum of the hyperbranched gold-silver-copper nanoclusters described in another embodiment of the present invention is shown. Figure 4 This is the UV-Vis absorption spectrum of the hyperbranched gold-silver-copper nanoclusters described in another embodiment of the present invention; Figure 5 This is a three-dimensional fluorescence spectrum of the hyperbranched gold-silver-copper nanoclusters described in another embodiment of the present invention; Figure 6 Fourier transform infrared contrast spectra of DPA, AuAgCu NCs and TPE-HPA@AuAgCu NCs in another embodiment of the present invention; Figure 7 This is a transmission electron microscope (TEM) image of TPE-HPA@AuAgCu NCs in another embodiment of the present invention; Figure 8 This is a TPE-HPA@AuAgCu NCs energy scattering X-ray spectral elemental mapping pattern in another embodiment of the present invention; Figure 9 The full spectrum of X-ray photoelectron energy (XPS) and the fine spectrum of single metal elements (Au 4f, Ag 3d, Cu 2p) of TPE-HPA@AuAgCu NCs are shown in another embodiment of the present invention. Figure 10 This is the UV spectrum of TPE-HPA@CuAgAu NCs reacted with different concentrations of hydrogen sulfide in another embodiment of the present invention; Figure 11 This is a fluorescence response kinetic curve of the reaction between TPE-HPA@CuAgAu NCs and 100μM hydrogen sulfide in another embodiment of the present invention; Figure 12 The fluorescence spectrum of TPE-HPA@CuAgAu NCs after reacting with different concentrations of hydrogen sulfide, excited at a wavelength of 360 nm, is shown in another embodiment of the present invention. Figure 13This is a standard curve of fluorescence intensity ratio at 483 nm and 624 nm versus hydrogen sulfide concentration in another embodiment of the present invention. Figure 14 This is a comparison diagram of the color and fluorescence changes of TPE-HPA@AuAgCu NCs test strips under fluorescent and ultraviolet lamps for different concentrations of hydrogen sulfide in another embodiment of the present invention; Figure 15 This is a standard curve of the total color difference value of the test strip under visible light versus the concentration of gaseous hydrogen sulfide in another embodiment of the present invention; Figure 16 This is a standard curve of the red / green channel ratio (R / G) of the test strip under 365nm ultraviolet light and the concentration of gaseous hydrogen sulfide in another embodiment of the present invention. Figure 17 This is a stability diagram of gold, silver and copper nanoclusters with different concentrations of hyperbranching loads at 7 days in another embodiment of the present invention. Figure 18 This is a fitted curve of standard color ΔE value and TVB-N in another embodiment of the present invention; Figure 19 This is a graph showing the TVB-N variation of beef at different time points at 25°C in another embodiment of the present invention; Figure 20 This is a graph showing the color and fluorescence changes of the test strips during the spoilage of beef at different time points at 25°C, according to another embodiment of the present invention. Figure 21 This is a graph showing the change in fluorescence intensity ratio before and after HS-incubation in the presence of different interfering substances in another embodiment of the present invention. Figure 22 The diagram shows the response characteristics of fluorescent probes (Cu NCs, AgCu NCs, AuCuNCs, AuAgCu NCs) at different concentrations to 40 μM H2S in another embodiment of the present invention. Detailed Implementation

[0022] The present invention will now be described in further detail with reference to the accompanying drawings, so that those skilled in the art can implement it based on the description.

[0023] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.

[0024] Example 1 Preparation of hyperbranched polyamide-amine: such as Figure 1Tris(2-aminoethyl)amine, 4-glycidyl ether tetraphenylene, and methanol were mixed in a molar ratio of 1:5:100 and reacted at 75 °C for 24 h under nitrogen protection to obtain the 4-glycidyl ether tetraphenylene-tris(2-aminoethyl)amine adduct. The obtained 4-glycidyl ether tetraphenylene-tris(2-aminoethyl)amine adduct was mixed with bisacryloylhexamethylenediamine in a molar ratio of 3:2.2 and subjected to Michael addition polymerization at 24 °C for 100 h under nitrogen protection to obtain the hyperbranched polyamide-amine.

[0025] Example 2 Preparation of hyperbranched gold, silver, and copper nanoclusters: such as Figure 1 Chloroauric acid solution, silver nitrate solution, and copper nitrate solution were mixed at a metal ion molar ratio of 1:1:1 to obtain a ternary metal ion mixture of gold, silver, and copper. Hyperbranched polyamide-amine prepared in Example 1 was added to the mixture as a ligand and stabilizer. After stirring until homogeneous, penicillamine was added as a reducing agent and the mixture was stirred at room temperature for 2 hours. The molar ratio of gold ions, silver ions, copper ions, hyperbranched polyamide-amine, and penicillamine was 1:1:1:0.04:108. After the reaction, the supernatant was removed by centrifugation, and the precipitate was purified and freeze-dried at -50°C to obtain hyperbranched gold-silver-copper nanoclusters powder, the structural schematic of which is shown in Figure 1. Figure 1 As shown.

[0026] The hyperbranched polyamide-amine prepared in Example 1 and the hyperbranched gold-silver-copper nanoclusters prepared in Example 2 were prepared into aqueous solutions. 2 mL of each solution was placed in a quartz sample cell. The fluorescence emission spectra of the probes at different excitation and emission wavelengths were measured using a fluorescence spectrophotometer. The parameters were set as follows: slit width of 10 nm, scan speed of 1200 nm / min, and photomultiplier tube voltage of 550 V. The fluorescence spectrum of the hyperbranched polyamide-amine is shown below. Figure 2 As shown, the fluorescence spectrum of hyperbranched gold, silver, and copper nanoclusters is as follows: Figure 3 As shown.

[0027] like Figure 2 As shown, at an excitation wavelength of 360 nm, hyperbranched polyamide-amine (TPE-HPA) exhibits a single emission peak at 483 nm. Figure 3 As shown, after one-pot synthesis of TPE-HPA@AuAgCu NCs, its fluorescence spectrum is a dual emission: in addition to retaining the emission peak of hyperbranched polyamide-amine at 483 nm, a strong new red fluorescence emission peak appears at 624 nm. The red fluorescence emission peak at 624 nm is attributed to the composite emission of the trimetallic nanoclusters.

[0028] The hyperbranched gold-silver-copper nanoclusters prepared in Example 2 were dissolved in an aqueous solution. 2 mL of this solution was placed in a quartz sample cell, and the absorption peak positions and absorbance were investigated using a UV / Vis spectrophotometer. The parameters were set as follows: scanning wavelength range of 200–800 nm, slit width of 2 nm, and data acquisition interval of 0.5 nm. The UV-Vis absorption spectrum of the hyperbranched gold-silver-copper nanoclusters is shown below. Figure 4 As shown, the three-dimensional fluorescence spectrum is as follows: Figure 5 As shown.

[0029] like Figure 4 and Figure 5 As shown, the UV-Vis absorption spectrum of TPE-HPA@AuAgCu NCs exhibits a continuous absorption band in the near-UV region, and the solution appears uniformly clear and transparent under sunlight. Figure 4 (Solution image above the UV-Vis absorption spectrum). As shown in the three-dimensional fluorescence spectrum, the excitation wavelength center of the probe is located in the 340-370 nm region, at E... m =483nm and E m Two independent fluorescence quantum emission centers are clearly visible at 624 nm, confirming the successful construction of the proportional fluorescence sensing platform.

[0030] 1.0 mg of D-penicillamine, gold-silver-copper trimetallic nanoclusters, and the hyperbranched gold-silver-copper nanoclusters prepared in Example 2 were respectively mixed and ground with 50.0 mg of dry KBr powder. The mixture was then pressed into transparent sheets using a tablet press. The tablets were placed in the sample window of an infrared spectrometer, and the spectral scanning range was set to 4000–600 cm⁻¹. -1 After removing background interference, the infrared absorption spectrum of the sample was obtained by scanning, and the results are as follows: Figure 6 As shown.

[0031] like Figure 6 As shown, the chemical bonds and coordination states were confirmed by Fourier transform infrared spectroscopy (FTIR). DPA at 2509 cm⁻¹ -1 The -SH stretching vibration peak disappeared in AuAgCu NCs, confirming that -SH dehydrogenation and covalent bonding with the metal (Au / Ag / Cu-SR), successfully synthesizing gold, silver, and copper nanoclusters. TPE-HPA@AuAgCu NCs showed a peak at 3174 cm⁻¹. -1 (NH) and 1618cm -1 The absorption peak at (C=O) was significantly enhanced and overlapped, confirming that TPE-HPA successfully loaded nanoclusters.

[0032] The hyperbranched gold-silver-copper nanoclusters obtained in Example 2 were uniformly dispersed in water. A 2 μL droplet of the suspension was placed onto the surface of a copper mesh support film. The copper mesh was placed in the sample window of a high-resolution transmission electron microscope (TEM). The accelerating voltage was set to 80-200 kV. The sample stage position was adjusted to locate the thin-film medium. The target area was located in low-magnification mode, and then the image was captured in high-resolution mode. The TPE-HPA@AuAgCuNCs TEM image is shown below. Figure 7 As shown, the elemental mapping of energy-scattered X-ray spectra is as follows: Figure 8 As shown.

[0033] like Figure 7 As shown, transmission electron microscopy (TEM) images indicate that the prepared TPE-HPA@AuAgCu NCs exhibit excellent monodispersity in the aqueous phase, with no large particle aggregation observed. The particle size follows a normal distribution, with an average particle size precisely distributed at approximately 2.8 nm; high-resolution transmission electron microscopy images (…) Figure 7 The upper right corner clearly shows highly developed internal lattice fringes, proving that it has a highly crystalline metallic core structure. (Example:) Figure 8 As shown, dark-field scanning transmission and elemental mapping images further confirm that the signals of copper, silver, and gold are highly overlapping in space and completely co-located at the nanoscale, strongly proving that the obtained product is a multi-metallic alloy nanocluster structure in which gold, silver, and copper coexist.

[0034] The hyperbranched gold-silver-copper nanoclusters obtained in Example 2 were ground to below 200 mesh and then formed into tablets using a tablet press. The samples were fixed to the sample stage with double-sided adhesive tape. The sample stage was placed in the ultra-high vacuum chamber of an X-ray photoelectron spectrometer. The full-spectrum scan was typically set with a pass energy of 80 eV, the narrow-spectrum scan with 20 eV, an energy step size of 0.1 eV, and a residence time of 50 ms per channel. Binding energies were calculated using calibration parameters, and energy spectra of elemental types, chemical states, and relative abundances were generated as shown below. Figure 9 As shown.

[0035] like Figure 9 As shown, the XPS full spectrum of TPE-HPA@CuAgAu NCs reveals characteristic peaks for Au, Ag, and Cu, proving that these three elements have been successfully introduced into the material. The high-resolution XPS spectra of each element further indicate that Au, Ag, and Cu all exist in the zero valence state (Au...). 0 Ag 0 Cu 0 )exist.

[0036] Example 3 Preparation of the hyperbranched gold, silver, and copper nanoclusters freshness test strip: Waterman test paper was cut into circular test strips with a diameter of 1 cm using a punch. The hyperbranched gold, silver, and copper nanoclusters powder obtained in Example 2 was prepared into a 1 mg / mL hyperbranched gold, silver, and copper nanoclusters solution. An appropriate amount of the hyperbranched gold, silver, and copper nanoclusters solution was accurately transferred and evenly dropped onto the circular test strips to ensure sufficient loading. The strips were then allowed to dry naturally at room temperature to obtain the hyperbranched gold, silver, and copper nanoclusters freshness test strip.

[0037] Example 4 (Detection of hydrogen sulfide, a marker of freshness in raw meat) Preparation of standard curve: The TPE-HPA@CuAgAu NCs powder obtained in Example 2 was prepared into an aqueous solution, and the UV-Vis absorption spectra after reacting with hydrogen sulfide of different concentrations (0~140μM) are shown below. Figure 10 As shown in the figure, the fluorescence response kinetics curve of the reaction between TPE-HPA@CuAgAuNCs and 100μM hydrogen sulfide is as follows. Figure 11 As shown.

[0038] like Figure 10 As shown, within the hydrogen sulfide concentration range of 0–140 μM, the UV-Vis absorption spectrum also exhibits a consistent pattern of fading and decrease (colorimetric channel). Figure 11 As shown, on the fluorescence response kinetic curve at 100 μM hydrogen sulfide, the fluorescence ratio I... 483 / I 624 The curve stabilized after 12 minutes, indicating that the chemical reaction reached the equilibrium endpoint within 12 minutes, demonstrating excellent rapid detection efficiency.

[0039] After preparing an aqueous solution from the TPE-HPA@CuAgAu NCs powder obtained in Example 2, it was reacted with different concentrations (0~100μM) of hydrogen sulfide (incubated at room temperature for 10~15 min), and the fluorescence spectra excited at a wavelength of 360nm are shown below. Figure 12 As shown in the figure. A standard curve was constructed with the ratio of fluorescence intensity at 483 nm to 624 nm as the ordinate and hydrogen sulfide concentration as the abscissa, as shown in the figure. Figure 13 As shown.

[0040] like Figure 12 As shown, with the increase of hydrogen sulfide concentration in the system, the red fluorescence emission peak of the nanoclusters at 624 nm is significantly quenched, while the fluorescence peak of the hyperbranched polyamide-amine at 483 nm decreases only slightly. Figure 13 As shown, the fluorescence intensity ratio (I) 483 / I 624Using y as the ordinate, within the concentration range of 20–80 μM, this ratio exhibits an excellent linear regression relationship with hydrogen sulfide concentration, with the fitted equation being y = 0.0011x + 0.1308 (R²). 2 =0.9877, detection limit is 0.4282 μM).

[0041] The test strips prepared based on Whatman filter paper in Example 3 show a comparison of color and fluorescence changes under visible light and 365nm ultraviolet light under different concentrations of gaseous hydrogen sulfide (0~549.98ppb). Figure 14 As shown.

[0042] The hyperbranched gold-silver-copper nanoclusters freshness test strips prepared in Example 3 were placed in gaseous hydrogen sulfide of different concentrations (0~549.98 ppb), and their RGB values ​​were extracted by photographing under fluorescent light and 365 nm ultraviolet light. The standard curve, with the total color difference of the test strip under visible light as the ordinate and the gaseous hydrogen sulfide concentration as the abscissa, is shown below. Figure 15 As shown, the standard curve with the red / green channel ratio (R / G) of the test strip under 365nm ultraviolet light as the ordinate and the concentration of gaseous hydrogen sulfide as the abscissa is as follows: Figure 16 As shown.

[0043] like Figure 15 As shown, under fluorescent light, the test strip gradually changes from white to yellow as the hydrogen sulfide concentration increases. Using images captured by a mobile phone, the total color difference value shows an excellent linear relationship with the gas concentration, with the regression equation being y = 0.0702x + 26.5788 (R²). 2 = 0.9812). For example... Figure 16 As shown, under 365nm ultraviolet light irradiation, the test strip exhibits a visible "red-to-blue" fluorescence color change. Images extracted via a smartphone show that the extracted red / green channel ratio (R / G value) exhibits a good negative linear correlation with the concentration of gaseous hydrogen sulfide, with the fitted equation being y = 1.4160 - 0.0015x(Rg). 2 =0.9703), this test strip can detect gaseous hydrogen sulfide.

[0044] Detection of hydrogen sulfide, a marker of freshness in fresh meat: The fresh meat sample to be tested is placed in a sealed container, and the hyperbranched gold-silver-copper nanocluster freshness test strip is brought into contact with the gas inside the container. The sample is incubated at room temperature for 10-15 min. The fluorescence intensity ratio of the hyperbranched gold-silver-copper nanocluster freshness test strip at 483 nm and 624 nm is recorded using 360 nm excitation. Alternatively, the fresh meat sample to be tested is placed in a sealed container, and the hyperbranched gold-silver-copper nanocluster freshness test strip is brought into contact with the gas inside the container. The sample is incubated at room temperature for 10-16 h, and the color change of the hyperbranched gold-silver-copper nanocluster freshness test strip is recorded by photographing. The RGB values ​​are extracted. The measured fluorescence intensity ratio at 483 nm and 624 nm or the color difference of the hyperbranched gold-silver-copper nanocluster freshness test strip is compared with the corresponding standard curve to obtain the hydrogen sulfide content in the sample, thereby determining the freshness of the fresh meat.

[0045] 1. Stability verification: The fluorescence signal of gold, silver, and copper nanoclusters with different concentrations of hyperbranched loading was recorded over one week using a fluorescence spectrophotometer to determine the time stability of the material. The results are as follows: Figure 17 As shown.

[0046] like Figure 17 As shown, gold, silver and copper nanoclusters with different concentrations of hyperbranching can be stored stably. Even after 7 days of storage, the fluorescence ratio remains unchanged. Therefore, it can be concluded that gold, silver and copper nanoclusters with different concentrations of hyperbranching have high stability.

[0047] 2. Accuracy Verification: Using beef sample freshness testing for verification, beef samples were stored at room temperature, and samples were taken at different storage time points. Two tests were performed simultaneously: First, the test strips were photographed using an image acquisition device, and the RGB color parameters of the test strip surface were extracted. The fitting curves of the standard color ΔE value and TVB-N are shown below. Figure 18 As shown; secondly, the content of volatile basic nitrogen (TVB-N) in the samples was determined according to the national standard method, and the correspondence between the color response of the test strip and the meat spoilage index was established to complete the accuracy verification of the freshness detection system. The changes of TVB-N in beef at different time points at 25℃ are shown in the figure. Figure 19 As shown, the color and fluorescence changes of the test strips during the spoilage process of beef at different time points at 25℃ are as follows: Figure 20 As shown.

[0048] Figure 18The figure shows the linear correlation curve between the color change of the test strip (expressed as ΔE value) and the actual volatile basic nitrogen (TVB-N) content of the meat product. By converting the RGB parameters of the test strip acquired by the image acquisition device into ΔE values ​​and jointly calibrating them with the TVB-N content determined by the national standard method, the results show a good linear regression relationship between the two (y=0.4392x+1.3365), with a correlation coefficient R0. 2 Up to 0.9514. (By...) Figure 19 The results show that the concentration of volatile basic nitrogen (TVB-N) in beef samples stored at 25℃ over time (0-40 h) indicates that the test strip monitoring system is highly correlated with the actual degree of sample spoilage. Figure 20 The results show the color changes (under natural light) and fluorescence quenching response (under ultraviolet light) of the test strips at different storage time points (0-40 h). As the storage time increases, the fluorescence intensity shows a clear quenching from strong to weak.

[0049] 3. Anti-interference verification: Common organic substances, amino acids, inorganic ions, and sulfur-containing interfering substances in the food system were selected as interfering matrices. The fluorescent probe was incubated separately with each interfering substance, and the fluorescence intensity ratio of the system was detected and recorded. Subsequently, hydrogen sulfide standard solution was added to each system, and the fluorescence intensity ratio was measured again. The influence of interfering substances on the probe's specific ability to recognize hydrogen sulfide was compared and analyzed. The changes in the fluorescence intensity ratio before and after HS-incubation under different interfering substances are shown below. Figure 21 As shown.

[0050] Figure 21 This invention demonstrates the effectiveness of the nanocluster fluorescent probe in the presence of various common food matrix interfering agents when hydrogen sulfide (HS-H2O) is introduced. ⁻ The ratio of fluorescence response before and after (I483 / I624) was compared. Experimental data comparison showed that, compared to the blank group and each interfering ion group, the addition of HS... ⁻ The groups after the test strip showed significant changes in fluorescence characteristic ratios, and the presence of interfering substances did not significantly affect their specific quenching effect, demonstrating the excellent anti-interference ability of the test strip in complex food matrices.

[0051] This application further investigated the response sensitivity of single-metal, bimetallic, and trimetallic nanoclusters to H2S, and the response characteristics of fluorescent probes (Cu NCs, AgCu NCs, AuCu NCs, AuAgCu NCs) at different concentrations (1 mg / ml, 1.5 mg / ml, 2 mg / ml, 2.5 mg / ml, 3 mg / ml, 3.5 mg / ml) to 40 μM H2S. The results are as follows: Figure 22 As shown. By Figure 22It can be seen that, compared with the single metal (Cu NCs) and bimetallic (AgCu NCs, AuCu NCs) systems, the AuAgCuNCs constructed in this invention exhibits superior fluorescence response sensitivity at various probe concentrations, verifying the contribution of the in-situ hybrid electronic structure of gold, silver and copper trimetallic compounds to enhancing the detection specificity and synergistic effect of the target analyte.

[0052] Therefore, the hyperbranched gold-silver-copper nanoclusters synthesized in Example 2 overcome the technical bias of uneven phase separation and nucleation caused by significant differences in standard redox potentials in traditional multimetallic co-reduction systems. Example 2, through the confinement effect of hyperbranched polyamide-amine, achieved for the first time an atomic-level alloying distribution of gold, silver, and copper atoms. Furthermore, the introduction of copper atoms, through in-situ hybridization of Au-Ag-Cu trigonal electron orbitals, induced efficient intermetallic charge transfer, endowing the trimetallic nanoclusters with a unique fluorescence luminescence mechanism distinct from single-metal / bimetallic systems. Moreover, the special microscopic electronic structure of the trimetallic nanoclusters exhibited a specific synergistic quenching effect on trace amounts of hydrogen sulfide, a marker of meat freshness, demonstrating significantly improved anti-interference ability and detection sensitivity in complex food matrices.

[0053] Comparative Example 1 Hyperbranched polyamide-amine was prepared according to the method disclosed in Chinese Patent CN118562125A, and thiol-based flavor-responsive hyperbranched polymer copper clusters were prepared according to the method disclosed therein. The specific method is as follows: Step 1: Prepare hyperbranched polyamide-amine containing disulfide bonds using tris(2-aminoethyl)amine and bisacryloylcysteine ​​as raw materials; Step 2: Introduce a tetraphenylethylene-type epoxy compound into the hyperbranched polyamide-amine containing disulfide bonds to obtain AIE-type hyperbranched polyamide-amine; Step 3: Use AIE-type hyperbranched polyamide-amine and glutathione as templates and reducing agents to reduce CuSO4 to obtain hyperbranched polymer copper cluster materials; Step 4: Introducing Ce into hyperbranched polymer copper cluster materials 3+ Ions were used to obtain ratio-type hyperbranched polymer copper cluster materials.

[0054] Comparative Example 1 used bisacryloylcysteine ​​as the raw material, while Example 1 used bisacryloylhexanediamine. The six carbon chains of hexanediamine provide longer hydrophobic spacer arms, which brings two direct benefits: First, it forms more hydrophobic internal cavities, and the reduction and nucleation processes of metal ions are partially confined within these hydrophobic cavities, forming a nano-reaction cage that can effectively limit the final size of the nanocluster and prevent its overgrowth. Second, the main chain is more stable. Hexanediamine is linked by stable amide bonds, avoiding the risk that monomers containing disulfide bonds (-SS-) will be broken by the reducing agent, thus ensuring the integrity of the reaction vessel. It is precisely because of the stable hyperbranched polymers provided in Example 1 or Example 2 that there are many cavities inside, with tertiary amine and amide groups closely arranged in the cavities, forming a high density of coordination sites. This allows for multi-point anchoring of gold, silver, and copper atoms with significant differences, which is crucial for overcoming the huge lattice stress of the trimetallic cluster and preventing its phase separation.

[0055] In the hyperbranched polyamide-amine synthesis method disclosed in Comparative Example 1, the main chain is polymerized from tris(2-aminoethyl)amine and bisacryloylcysteine, and the main chain contains disulfide bonds (-SS-). In the hyperbranched polyamide-amine synthesis methods disclosed in Examples 1 and 2, the main chain is polymerized from an adduct containing tetraphenylethylene units and bisacryloylhexanediamine. The main chain lacks disulfide bonds, and the TPE units are directly embedded as the backbone. This is because the disulfide bonds in Comparative Example 1 are intended to reserve anchor points for subsequent grafting, but their chemical reactivity makes them easily reduced and broken when a reducing agent is used, leading to polymer disintegration. Examples 1 and 2 use stable amide bonds to construct a pure hydrocarbon backbone, resulting in higher chemical stability and providing a reliable reaction vessel for the preparation of trimetallic clusters.

[0056] The hyperbranched polyamide-amine synthesis method disclosed in Comparative Example 1 employs a strategy of polymerization followed by grafting. First, a polymer backbone containing disulfide bonds is synthesized, and then a TPE-type epoxy compound is attached to the polymer side chains via a post-modification reaction. The hyperbranched polyamide-amine synthesis methods disclosed in Examples 1 or 2 employ an in-situ copolymerization strategy. The TPE moiety is directly used as one of the polymer monomers in the form of an adduct containing tetraphenylethylene moiety, and is embedded into the polymer backbone during polymerization. The post-grafting method in Comparative Example 1 struggles to ensure uniform distribution of TPE moiety across the polymer branches, while the in-situ copolymerization backbone synthesis method in Example 1 ensures a uniform and dense distribution of TPE moiety throughout the hyperbranched structure. Furthermore, as part of the backbone, the intramolecular rotation of TPE is more constrained; a more "crowded" structure is more effective at illuminating the AIE effect, which is a significant advantage in preparing high-brightness solid-state fluorescent materials.

[0057] Most importantly, the synthesis method in Example 1 or Example 2 involves the direct participation of the TPE-containing adduct in Michael addition, meaning that the TPE motif is embedded in the polymer's main chain backbone. Compared to Comparative Example 1, which synthesizes and then grafts onto side chains, the main chain synthesis route of this application has two significant advantages: First, it has a more sensitive molecular brake. As part of the main chain, the intramolecular rotation of TPE is subject to extremely rigid constraints by the hyperbranched structure. In solution, the growth of trimetallic nanoclusters further locks the TPE motif, resulting in rapid and intense fluorescence. Therefore, the fluorescence reaction incubation time for Comparative Example 1 requires 30 minutes, while the fluorescence reaction in this application only requires 10-15 minutes. Second, it effectively prevents solid-state fluorescence quenching. As shown in Example 4, this application solves the fatal problem of traditional fluorophores quenching due to aggregation on dry test strips, ensuring the usability of the test strip in the solid state, whereas Comparative Example 1 can only detect in solution.

[0058] In terms of nanocluster preparation, Comparative Example 1 uses single copper, followed by the introduction of rare earth cerium ions (Ce). 3+ Example 1 describes a method for constructing a ratiometric sensor using glutathione (GSH) as the primary reducing agent. However, the significant differences in redox potentials among gold, silver, and copper ions make the formation of a homogeneous alloy, rather than individual nucleation or a core-shell mixture, a recognized challenge in the industry. Comparative Example 1 uses glutathione, a highly reducing agent. When faced with the three noble metal ions with vastly different reactivity (gold, silver, and copper), the strong reducing agent causes the most easily reduced gold ion to nucleate first, making co-reduction impossible. Furthermore, glutathione's strong reducing properties attack the disulfide bonds on its own polymer backbone, causing the hyperbranched polymer template to disintegrate on the spot, ultimately preventing the synthesis of nanoclusters. Example 2 describes a one-step method for preparing gold, silver, and copper trimetallic nanoclusters using penicillamine as the reducing agent. Penicillamine is a mild reducing agent that balances the time difference in the reduction of gold, silver, and copper ions, creating the possibility for their orderly reduction into atoms within the polymer template and the formation of alloy clusters, thus synthesizing trimetallic nanoclusters. The synthesis method in Example 2 is not a simple superposition of metal types, but rather achieves electronic synergy and lattice hybridization among gold, silver, and copper at the nanoscale, thereby giving rise to stronger fluorescence, better stability, or more sensitive response performance that are not found in single-metal or bimetallic systems.

[0059] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.

Claims

1. The application of hyperbranched gold, silver, and copper nanoclusters freshness test strips in the detection of hydrogen sulfide, a marker of freshness in fresh meat, characterized in that... The hyperbranched gold-silver-copper nanoclusters freshness test strip reacts with hydrogen sulfide, simultaneously generating a fluorescence channel response (decreased fluorescence intensity) and a colorimetric channel response (color change from light to yellow). The fluorescence channel response refers to dual-emission fluorescence characteristics at 483 nm and 624 nm under 360 nm excitation. The hyperbranched gold-silver-copper nanoclusters freshness test strip is prepared using the following method: S1. Tri(2-aminoethyl)amine, 4-glycidyl ether tetraphenylene, and methanol are mixed in a molar ratio of 1:4~6:90~120 and reacted at 65~80 °C for 21~27 h under nitrogen protection to obtain the 4-glycidyl ether tetraphenylene-tri(2-aminoethyl)amine adduct. S2. The 4-glycidyl ether tetraphenylethylene-tris(2-aminoethyl)amine adduct obtained in S1 is mixed with bisacryloylhexanediamine at a molar ratio of 3:2.2 and subjected to Michael addition polymerization at 21-27 °C for 90-102 h under nitrogen protection to obtain hyperbranched polyamide-amine. S3. Mix chloroauric acid solution, silver nitrate solution and copper nitrate solution at a metal ion molar ratio of 1:1:1 to obtain a gold-silver-copper ternary metal ion mixture. S4. Add the hyperbranched polyamide-amine obtained in S2 as a ligand and stabilizer to the gold-silver-copper ternary metal ion mixture obtained in S3. After stirring evenly, add penicillamine as a reducing agent and stir at room temperature for 1-2 h. After the reaction is completed, centrifuge to remove the supernatant, purify the precipitate and freeze dry at -40 to -50℃ to obtain hyperbranched gold-silver-copper nanocluster powder. S5. Prepare a solution from the hyperbranched gold, silver and copper nanoclusters powder obtained in S4, and uniformly drop it onto Waterman test paper. Dry at room temperature to obtain the hyperbranched gold, silver and copper nanoclusters freshness test strip. In step S4, the molar ratio of gold ions, silver ions, copper ions, hyperbranched polyamide-amine, and penicillamine is 1:1:1:0.04:

108.

2. The application of the hyperbranched gold, silver, and copper nanoclusters freshness test strip as described in claim 1 in the detection of hydrogen sulfide, a marker of freshness in fresh meat, is characterized in that... In step S2, bisacryloylhexanediamine is prepared by the following method: Sodium hydroxide and hexamethylenediamine were mixed evenly. Acryloyl chloride was slowly added dropwise to the mixture of sodium hydroxide and hexamethylenediamine under stirring in an ice bath at 0°C. The molar mixing ratio of sodium hydroxide, hexamethylenediamine and acryloyl chloride was (1.8~2.2):1:(1.8~2.2).

3. The application of the hyperbranched gold, silver, and copper nanoclusters freshness test strip as described in claim 2 in the detection of hydrogen sulfide, a marker of freshness in fresh meat, is characterized in that... In step S5, the hyperbranched gold, silver and copper nanoclusters are prepared into a solution with a concentration of 1~4 mg / mL.

4. Hyperbranched gold-silver-copper nanoclusters, characterized in that, The hyperbranched gold-silver-copper nanoclusters are prepared using steps S1 to S4 of the preparation method described in claim 1. The hyperbranched gold-silver-copper nanoclusters are formed by a one-pot reaction of gold ions, silver ions, and copper ions, using hyperbranched polyamide-amine as a ligand and stabilizer and penicillamine as a reducing agent. The hyperbranched gold-silver-copper nanoclusters exhibit dual emission fluorescence characteristics at 483 nm and 624 nm under 360 nm excitation.

5. A test strip for the freshness of hyperbranched gold, silver, and copper nanoclusters, characterized in that... The hyperbranched gold, silver and copper nanoclusters freshness test strip is prepared using the preparation method described in claim 1.

6. A method for detecting hydrogen sulfide, a marker of freshness in fresh meat, using the hyperbranched gold-silver-copper nanocluster freshness test strip as described in claim 5, characterized in that... include: A1. Sodium hydrosulfide solution of hydrogen sulfide standard at different concentrations was added dropwise to hyperbranched gold-silver-copper nanoclusters solution and incubated at room temperature for 10-15 min. The solution was excited at a wavelength of 360 nm, and the fluorescence intensity of the hyperbranched gold-silver-copper nanoclusters solution at 483 nm and 624 nm was recorded. A standard curve of fluorescence intensity ratio at 483 nm and 624 nm versus hydrogen sulfide concentration was prepared. A2. Prepare sodium hydrosulfide solutions of hydrogen sulfide standard at different concentrations, place them in a sealed container, and allow the hyperbranched gold, silver, and copper nanoclusters freshness test strip to contact the gas in the container. Incubate at room temperature for 10-16 hours, and photograph and record the color changes of the hyperbranched gold, silver, and copper nanoclusters freshness test strip under fluorescent light and 365nm ultraviolet light. Extract the RGB values ​​and prepare a standard curve of color difference versus hydrogen sulfide concentration for the hyperbranched gold, silver, and copper nanoclusters freshness test strip under fluorescent light, or a standard curve of red / green channel ratio versus hydrogen sulfide concentration for the hyperbranched gold, silver, and copper nanoclusters freshness test strip under ultraviolet light. A3. Place the fresh meat sample to be tested in a sealed container, and allow the hyperbranched gold-silver-copper nanocluster freshness test strip to contact the gas inside the container. Incubate at room temperature for 10-15 min. Excite the test strip at a wavelength of 360 nm and record the fluorescence intensity ratio at 483 nm and 624 nm. Alternatively, place the fresh meat sample to be tested in a sealed container, and allow the hyperbranched gold-silver-copper nanocluster freshness test strip to contact the gas inside the container. Incubate at room temperature for 10-16 h. Take photos to record the color changes of the hyperbranched gold-silver-copper nanocluster freshness test strip under fluorescent light and 365 nm ultraviolet light, and extract the RGB values. A4. Compare the fluorescence intensity ratio at 483 nm and 624 nm measured in step A3, or the color difference of the hyperbranched gold, silver and copper nanoclusters freshness test strip under fluorescent light, or the red / green channel ratio of the hyperbranched gold, silver and copper nanoclusters freshness test strip under ultraviolet light, with the corresponding standard curve obtained to obtain the hydrogen sulfide content in the sample to be tested, thereby determining the freshness of fresh meat.

7. A method for detecting hydrogen sulfide using ratiometric fluorescence, characterized in that, Using the hyperbranched gold-silver-copper nanocluster freshness test strip as described in claim 5, the fluorescence intensity ratio at 483 nm and 624 nm was recorded by excitation at a wavelength of 360 nm, and the hydrogen sulfide concentration was quantitatively detected based on the change in the fluorescence intensity ratio at 483 nm and 624 nm.

8. A ratiometric method for detecting hydrogen sulfide, characterized in that, The hyperbranched gold, silver and copper nanoclusters freshness test strip described in claim 5 is brought into contact with the hydrogen sulfide gas to be tested or the volatile gas of the fresh meat sample. The color change of the test strip is photographed and the RGB values ​​are extracted. The color difference value of the hyperbranched gold, silver and copper nanoclusters freshness test strip is used as the response signal, and the hydrogen sulfide concentration is quantitatively detected based on the change in the color difference value.

Citation Information

Patent Citations

  • Over-branched polyamidoamine and metal nano compound as well as preparation method and uses thereof

    CN101225227B

  • Hydrogen sulfide detection method based on metal nanocluster

    CN114047169A

  • Preparation method of ratio-type fluorescent gold-copper nanocluster, product and application of ratio-type fluorescent gold-copper nanocluster

    CN114907837A

  • Thiol flavor response type hyperbranched polymer copper cluster as well as preparation method and application thereof

    CN118562125A